Penyelesaian Tindak Pidana Ringan Melalui Komunikasi Mediasi Lembaga Adat - Musrizal Musrizal; Syamsul Bahri; Maisarah Maisarah (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2020)
This research is important to explain about minor criminal acts, which are acts committed by someone who violates the public interest which is threatened with sanctions or fines. The legal basis for the settlement of minor crimes that can be carried out by the Adat Qanun Institution Number 9 of 2008 concerning the Development of Customary Life, Article 13 Paragraph (1) regulates that there are 18 cases or disputes that are delegated resolutions through the Adat Court in Aceh, as well as Court Regulations. Agung (Perma) Number 2 of 2012 regulates the limit on the value of minor crimes. The settlement of minor crimes committed by the Gampong Customary Institution always makes it easier for the parties in the settlement process. The settlement carried out by the Customary Institution is to hold deliberations and summon the parties to facilitate the settlement process for the minor criminal case. The settlement of the crime is carried out at the meunasah in a fast and easy way and does not require money. Meanwhile, the sanctions given by the Gampong Customary Institution are also in accordance with the capabilities and habits prevailing in the local community. The role of the Customary Institution in every dispute resolution, where Adat always strives to maintain a balance between the reporter and the reported and the sanctions that are wise and fair for both parties, so that the parties get a sense of justice and no one feels disadvantaged.Penelitian penting untuk mengkaji tentang tindak pidana ringan adalah perbuatan yang dilakukan oleh seseorang yang melanggar kepentingan umum yang diancam dengan sanksi atau denda. Landasan hukum terhadap penyelesaian tindak pidana ringan yang dapat dilakukan oleh Lembaga Adat Qanun Nomor 9 Tahun 2008 Tentang Pembinaan Kehidupan Adat Istiadat, dalam Pasal 13 Ayat (1) mengatur ada 18 kasus atau perselisihan yang dilimpahkan penyelesaiannya melalui Peradilan Adat di Aceh, serta juga Peraturan Mahkamah Agung (Perma) Nomor 2 Tahun 2012 mengatur tentang batasan nilai tindak pidana ringan. Penyelesaian tindak pidana ringan yang dilakukan oleh Lembaga Adat Gampong senantiasa memudahkan para pihak dalam proses penyelesaian tersebut. Penyelesaian yang dilakukan secara Lembaga Adat adalah dengan mengadakan musyawarah serta memanggil para pihak untuk memudahkan proses penyelesaian perkara tindak pidana ringan tersebut. Penyelesaian tindak pidana tersebut dilakukan di meunasah dengan cara cepat dan mudah serta tidak membutuhkan biaya. Sedangkan sanksi yang diberikan oleh Lembaga Adat Gampong juga sesuai dengan kemampuan dan kebiasaan yang berlaku dalam masyarakat setempat. Peranan Lembaga Adat dalam setiap penyelesaian sengketa, dimana Adat selalu berupaya untuk menjaga keseimbangan antara pelapor dan terlapor serta sanksi yang bijak dan adil bagi kedua belah pihak, sehingga para pihak mendapatkan rasa keadilan serta tidak ada yang merasa dirugikan.